Gugatan Pembatalan Pengangkatan Anak/Adopsi : Studi Kasus di Pengadilan Kota Bogor No 143/Pdt.G/2021/PN Bogor - Nurhalimah Nurhalimah; Zaenal Arifin; Zairin Noor (Jurnal Hukum dan Demokrasi (JHD), 2023)
Children are the heirs and successors of the family lineage. Therefore, if a marriage has not or is not blessed with children, then adoption or adoption is held. The definition of adoption can be seen in etymology, terminology, and according to legal experts. But not all families get to enjoy raising a child like other families. In some families, by the power of God, where the desire to have children even after years of marriage has not been blessed, while the desire to have children is very great. So as a result, the descendants of the family will be threatened with extinction and break up if no one continues the family tree and family relatives. If this event occurs, there is a possibility of adopting a child whose origin could be from a relative, family or adopting a child who has nothing to do with family relatives (adopted) to become the successor of the lineage of the family concerned. In this study, the authors used the Sociological Juridical approach, combining juridical/legal rules combined with social facts related to the problem or object under study, namely the case of lawsuits for canceling child adoption and the type of research is descriptive research, the research aims to describe systematically, factual, and accurate, to a particular object. Regulations regarding child adoption have existed in Indonesia since the Dutch East Indies era in the form of Staadsblad No. 129 of 1917 which regulates the adoption of children which specifically applies to Chinese people until the current law, namely Government Regulation of the Republic of Indonesia No. 54 of 2007 concerning Implementation of Child Adoption and Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection, but none of these regulations regulate the cancellation of child adoption, meaning that in Indonesia there is a legal vacuum related to regulations which regulates the cancellation of child adoption.